Therapeutic Targets for the Treatment of Cardiac Fibrosis and Cancer: Focusing on TGF-β Signaling - Parichatikanond, Warisara; Luangmonkong, Theerut; Mangmool, Supachoke; Kurose, Hitoshi (Frontiers in Cardiovascular Medicine, 2020)
Transforming growth factor-β (TGF-β) is a common mediator of cancer progression and fibrosis. Fibrosis can be a significant pathology in multiple organs, including the heart. In this review, we explain how inhibitors of TGF-β signaling can work as antifibrotic therapy. After cardiac injury, profibrotic mediators such as TGF-β, angiotensin II, and endothelin-1 simultaneously activate cardiac fibroblasts, resulting in fibroblast proliferation and migration, deposition of extracellular matrix proteins, and myofibroblast differentiation, which ultimately lead to the development of cardiac fibrosis. The consequences of fibrosis include a wide range of cardiac disorders, including contractile dysfunction, distortion of the cardiac structure, cardiac remodeling, and heart failure. Among various molecular contributors, TGF-β and its signaling pathways which play a major role in carcinogenesis are considered master fibrotic mediators. In fact, recently the inhibition of TGF-β signaling pathways using small molecule inhibitors, antibodies, and gene deletion has shown that the progression of several cancer types was suppressed. Therefore, inhibitors of TGF-β signaling are promising targets for the treatment of tissue fibrosis and cancers. In this review, we discuss the molecular mechanisms of TGF-β in the pathogenesis of cardiac fibrosis and cancer. We will review recent in vitro and in vivo evidence regarding antifibrotic and anticancer actions of TGF-β inhibitors. In addition, we also present available clinical data on therapy based on inhibiting TGF-β signaling for the treatment of cancers and cardiac fibrosis.